Dissemination of geriatric emergency department accreditation in a large health system. Issue 6 (7th September 2020) - Liberman, Tara; Roofeh, Regina; Herod, Sarah Healey; Maffeo, Victoria; Biese, Kevin; Amato, Teresa
Abstract: The population of older adults in the United States is expanding rapidly. With this expansion, the healthcare system, and emergency departments (EDs) in particular, should provide geriatric‐focused care tailored to the needs of this population. To this end, the American College of Emergency Physicians (ACEP) released a geriatric emergency department accreditation (GEDA) to certify EDs that have the staffing, training, and resources to provide high‐quality, geriatric‐focused, emergent care. Our healthcare system set out to achieve the GEDA at all system hospitals using a service‐line approach and standardized policies. The implementation and application process was completed through strong partnerships between the Emergency Medicine Service Line and the Division of Geriatrics and Palliative Medicine. Further partnerships with ACEP were vital to completing the application process and using a standardized application. Through these partnerships, all 17 of our system hospitals achieved tier 3 accreditation. Through this process, we were able to identify opportunities to improve the care provided to older adults in the ED, particularly via staff education. We also gathered lessons learned for system‐level accreditation, including fostering close partnerships, meeting the unique needs of each ED, and strategically planning when and where to increase tier levels. This practice of large‐scale, system‐wide standardization, rather than individual site implementation, is an effective measure to provide geriatric‐focused care to the large and growing population of older adults.